Structure-property correlation in stabilizing axial magnetic anisotropy in octahedral Co(II) complexes - Tripathi, Shalini; Vaidya, Shefali; Ahmed, Naushad; Andreasen Klahn, Emil; Cao, Huibo; Spillecke, Lena; Koo, Changhyun; Spachmann, Sven; Klingeler, Rüdiger; Rajaraman, Gopalan; Overgaard, Jacob; Shanmugam, Maheswaran (Cell reports. Physical science, 2021)
Stabilizing an easy axis of magnetization in an octahedral Co(II) complex is an extremely challenging task, which is evident from reports that more than 90% possess easy-plane anisotropy. Here, we report a six-coordinate complex, [Co(L1)4(Cl)2] (1, L1 = thiourea [H2N-CS-NH2]), that exhibits a D value of −63(10) cm−1. The presence of an easy axis of magnetization associated with 1 is experimentally proven by detailed magnetic studies and polarized neutron diffraction studies, and the experimental observations are well corroborated by theoretical calculations. From the combined experimental and theoretical investigations (on 1 and many model systems), we unveil the parameters that control stabilization of negative D in a thermodynamically favorable and air-stable Co(II) ion in the common distorted octahedral geometry. This study paves the way for overcoming the current impediments to alleviate the easy axis of magnetization using rational ligand choice.